STRATEGI KEBUDAYAAN QUR’ANI HASYIM ASY’ARI YANG RAHMATAN LIL ALAMIN - Sholeh, Muhamad (IAIN Tulungagung, 2019)
The article in the hands of this reader is none other than a reflection of our Islam in Indonesia. This reflection aims to arouse the spirit that surges in the body of the Nahdliyin (NU) people. Which is actually written in it is a mixture of Qanun Asasi (Al-Qur'an and Hadith) KH. Hasyim Asy'ari with a country full of culture. In fact, it is used to formulate the Culture Strategy of Qur'ani in order to save the Unitary Republic of Indonesia (Unitary State of the Republic of Indonesia) is also a syifa ?(medicine) for all people. That the true Cultural Strategy is always used from time to time in order to solve different problems with one main foundation, namely the Qur'an and the Hadith. Because Al-Qur'an is final at the same time Hadith has also been given. So as a Muslim, he should make it as a benchmark that needs to be re-learned in the arena of modern Muslims. So that in Islam we are not rude, angry, liberal, radical, and so on. In conclusion, a true Islam must truly blend with culture, by taking the core of health (the verse of God) combined with real reality. So the concept of rahmatan lil alamin is truly soothing for all humans. Keyword: Cultural Strategy, Al-Qur'an, KH. Hasyim Ash'ari. Artikel yang ada ditangan pembaca ini bukan lain dan tidak bukan merupakan refleksi dari kita ber-Islam di Indonesia. Refleksi ini bertujuan untuk membangkitkan semangat yang menggelora dalam tubuh umat Nahdliyin (NU). Yang sejatinya tulisan didalamnya merupakan percampuran antara Qanun Asasi (Al-Qur?an dan Hadits) KH. Hasyim Asy?ari dengan realias negara yang penuh dengan budaya. Notabene dipakai untuk merumuskan Strategi KebudayaanQur?ani demi untuk menyelamatkan NKRI (Negara Kesatuan Republik Indonesia) juga merupakan syifa? (obat) bagi semua umat. Bahwa sejatinya Strategi Kebudayaanmemang selalu dipakai dari masa-ke masa demi menyelesaikan masalah yang berbeda dengan satu landasan utama yakni Al-Qur?an dan Hadits. Dikarenakan Al-Qur?an sudah final sekaligus Hadits juga sudah diberikan. Maka sebagi seorang Muslim hendaknya menjadikan ia sebagai patokan yang perlu dirasakan ulang kehikmahannya dalam kancah Muslim modern. Sehingga dalam kita ber-Islam tidak ada sebutan kasar, marah, liberal, radikal, dan lain sebaginya. Kesimpulannya Islam yang benar-benar Islam sejatinya harus berbaur dengan kebudayaan, dengan mengambil inti kemanfatan (ayat Allah) berpadu dengan realitas yang nyata. Sehingga konsep rahmatan lil alamin memang benar ?benar menyejukkan bagi semua manusia. Kata Kunci: Strategi Kebudayaan, Al-Qur?an, KH. Hasyim Asy?ari.